Evaluation of Rain Shelter Cultivation Mode Effects on Microecological Environment of Mountain Cultivated Ginseng Rhizosphere - Yinan Yu; Jingzi Piao; Siyi Guo; Bing Li; Zibo Li; Rujun Zhou (Agronomy)
Rainfall, particularly in continental climates with a monsoonal tendency, impacts the microbial niches during the growth of mountain cultivated ginseng. With shifts in the microbial community, diseases in ginseng cultivated and protected under rain shelter conditions may ultimately be altered. Such cultivation may influence microflora dynamics through variations in meteorological parameters; however, this is not yet clear. The present study found that rain shelter cultivation affected the distribution of fungal communities within mountain cultivated ginseng. This led to an improved community structure in the ginseng rhizosphere, characterized by the proliferation of antagonistic fungi and a reduction in pathogenic fungi. A correlation analysis of meteorological factors found that soil temperature and humidity were the primary meteorological factors affecting mountain cultivated ginseng. It is evident that rain shelter cultivation regulated the microecological environment of the mountain cultivated ginseng’s rhizosphere and resulted in positive outcomes. A disease investigation supported this finding. The incidence of ginseng root diseases, such as rust and root rot, was reduced by 5–6%. The incidence of ginseng leaf diseases, including gray mold and black spot, was reduced by 5–10%. This research provides evidence to address the dynamics of microbial ecology under rain shelter cultivation and its benefits for sustainable mountain cultivated ginseng management.